Effect of pressure on the properties of a NASICON Li1.3Al0.3Ti1.7(PO4)3 nanofiber solid electrolyte. Issue 23 (7th June 2021) - La Monaca, Andrea; Girard, Gabriel; Savoie, Sylvio; Demers, Hendrix; Bertoni, Giovanni; Krachkovskiy, Sergey; Marras, Sergio; Mugnaioli, Enrico; Gemmi, Mauro; Benetti, Daniele; Vijh, Ashok; Rosei, Federico; et al.
Abstract : A study on how the pressure applied to electrospun NASICON-like Li1.3 Al0.3 Ti1.7 (PO4 )3 nanofibers affects their purity, porosity and ionic conductivity. Abstract : We report the effect of pressure on a membrane made of dense electrospun NASICON-like Li1.3 Al0.3 Ti1.7 (PO4 )3 (LATP). The properties and performance of the pressed LATP nanofibers were investigated and compared with those of pristine LATP nanofibers. While the applied pressure affects the purity and homogeneity of LATP, it is beneficial for ionic transport across the solid electrolyte. The presence of impurity phases as well as the decrease of porosity results in a two order of magnitude higher ionic conductivity at room temperature (3 × 10 −5 S cm −1 ) which is promising to replace bulk NASICON materials in energy storage devices.